2007
DOI: 10.1111/j.1651-2227.2007.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and recurrent pancreatitis in children: etiological factors

Abstract: The clinical picture and etiological factors were similar in both groups. Since one out of every three children with acute pancreatitis in this series presented recurrences, it was not considered to be a 'benign disease'. Fifteen different etiological factors were identified in two-thirds of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
87
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 20 publications
(34 reference statements)
14
87
0
5
Order By: Relevance
“…Sánchez-Ramirez et al 18 observaram 36 crianças com diagnóstico de PA e 19 com pancreatite recorrente, concluindo que em cerca de 35% dos casos a causa era idiopática, mesmo após investigação completa, conforme já apontado em estudos anteriores, que descrevem valores entre 10-20% de PA idiopática em crianças 19,20 . Ainda, evidências recentes apontam que parte significativa dos casos de pancreatite idiopática em crianças está relacionada a mutações genéticas diversas 18,21 , responsáveis pela ocorrência da doença diretamente ou predisponentes desta, muitas das quais localizadas no braço longo do cromossomo 7 (7q35), onde muitos genes envolvidos com a transcrição e regulação do tripsinogênio estão localizados 22 .…”
Section: Pancreatite Aguda Recorrente Hereditária: Aspectos Genéticosunclassified
See 1 more Smart Citation
“…Sánchez-Ramirez et al 18 observaram 36 crianças com diagnóstico de PA e 19 com pancreatite recorrente, concluindo que em cerca de 35% dos casos a causa era idiopática, mesmo após investigação completa, conforme já apontado em estudos anteriores, que descrevem valores entre 10-20% de PA idiopática em crianças 19,20 . Ainda, evidências recentes apontam que parte significativa dos casos de pancreatite idiopática em crianças está relacionada a mutações genéticas diversas 18,21 , responsáveis pela ocorrência da doença diretamente ou predisponentes desta, muitas das quais localizadas no braço longo do cromossomo 7 (7q35), onde muitos genes envolvidos com a transcrição e regulação do tripsinogênio estão localizados 22 .…”
Section: Pancreatite Aguda Recorrente Hereditária: Aspectos Genéticosunclassified
“…Mais de 1.000 mutações do gene regulador da condutância transmembrana da fibrose cística (CFTR) foram descritas 15,18,23 como causadoras da doença de caráter autossômico recessivo, à medida que tornam deficitária a função dos canais de cloreto regulados por monofosfato cíclico de adenosinae, ainda, a secreção de bicarbonato de sódio, que, somadas, alteram o equilíbrio na diluição e alcalinização da secreção pancreática, permitindo a formação de plugs proteicos intraductais por acúmulo de líquido mais viscoso e predispondo à ativação de enzimas intrapancreáticas e consequente autodigestão do parênqui-ma. Estima-se que mesmo indivíduos heterozigotos para as mutações no gene CFTR tenham um risco aumentado em 40 vezes no desenvolvimento de pancreatite crôni-ca 22 .…”
Section: Pancreatite Aguda Recorrente Hereditária: Aspectos Genéticosunclassified
“…In contrast with adults, in whom alcohol and gallstones are the most common causes of CP, etiology in children is diverse [1,3,13]. The most common cases seen in our department resulted from gene mutations, anatomic anomalies of the pancreatic duct, biliary tract diseases and lipid disturbances [4].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years an increase in the number of children with CP has been observed in our hospital as well as in other pediatric centers worldwide [1,3,4,13]. In contrast with adults, in whom alcohol and gallstones are the most common causes of CP, etiology in children is diverse [1,3,13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increase in the number of paediatric AP cases in single institutions has been reported by centres in the USA, [2][3][4][5] Australia, 6 and Mexico. 7 However, these studies are retrospective reviews and the incidence of AP is usually reported as an absolute number of cases per centre per year at individual referral institutions.…”
Section: Introductionmentioning
confidence: 99%